Pengaruh Konformitas, Tekanan Teman Sebaya dengan Berita Palsu yang Dimediasi oleh Pengambilan Keputusan pada Remaja sebagai Korban - Fernandez, Germanikus (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2025)
This study aims to look at the influence of conformity, peer pressure on fake news mediated by decision making in adolescent victims at SMKN “X” in Kupang City. The research method used is quantitative method with correlational research design and using regression analysis. Respondents in this study totaled 157 students consisting of 86 males, and 71 females aged 15-19 years at SMKN “X” in Kupang City using probability sample technique, namely systematic sample. Data collection was carried out using a fake news adaptation scale, namely Questions on Fake news Identification (QFI) and a scale measuring peer pressure, namely the Peer Pressure Inventory, while decision making, using the Melbourne Decision Making Questionnaire which has been tested for reliability and validity. The results of this study show that, there is an influence of conformity on fake news with a Sig value of 0.000; there is also an influence of peer pressure on fake news with a sig value of 0.000. In addition, the effect of conformity will be greater if the presence of decision making as a moderator with a sig value of 0.002, while in peer pressure it will be greater if the presence of decision making as a moderator with a sig value of 0.000. Thus, decision making is a booster effect that strengthens the influence of conformity and peer pressure on fake news on teenagers as victims.